Power, empowerment and children in Dhaka's poor urban communities : understanding and measuring children's empowerment : a thesis presented in partial fulfilment of requirements for the degree of Master of International Development at Massey University, Palmerston North, New Zealand - Hamilton, Harley (Massey University, 2019)
This thesis is about children, power and empowerment. It seeks to both understand and measure power and empowerment from the perspectives of poor urban children living in Dhaka, Bangladesh. Children have been largely overlooked in development studies literature and although empowerment and measurement have been mainstreamed into development practice, children’s perspectives on these two essentially contested concepts are marginal. This thesis contributes to existing understandings of children’s power and empowerment, with a specific focus on poor urban children living in Dhaka. To do this, this thesis draws on two competing research paradigms, those of interpretivism and positivism respectively. I show how these two research paradigms can be brought together into a single mixed methods methodology when employed to answer distinct, but related research questions. This enabled me to use a combination of qualitative and quantitative methods and analytical strategies: task-based visual methods employed in a creative art and storytelling workshop; a qualitative thematic analysis; indicator construction; a survey and a descriptive statistical analysis. Bringing together these two competing research paradigms allows for the in-depth, contextual knowledge that qualitative research uncovers, with the ability to use this knowledge as a basis for measurement. In this thesis, I draw on empirical evidence uncovered through my research methods and insights from post-structuralism, development sociology and the literature on the relationality of childhood to argue that power can be viewed as boundaries to action. Boundaries of power exist as social structures that demarcate fields of action, possibility and imagination and are not resources that any actor has or uses but instead exist as boundaries which constrain all actors. I explore five boundaries of power that were highlighted by my research participants: personal relationships with family and friends; access to material and financial resources; the natural environment; education and children’s work. I present 34 indicators of empowerment I created that were derived from these boundaries of power. I discuss the survey and descriptive statistical analysis I undertook to measure these indicators with a small group of poor urban children. These indicators are therefore context specific and intended to be relevant and meaningful to those who are to be affected by development. They are a tool that could be used by development practitioners to measure a baseline of the relative empowerment or disempowerment of children in Dhaka and to track and measure change over time. Drawing on both my qualitative and quantitative findings, I show that viewing power as boundaries is not to claim that all power relations are equal. Instead I show that actors are placed in differential positions within power’s boundaries and have different channels for action. I suggest, therefore, that empowerment can be reconceptualized as a temporal issue that should first seek to expand the channels for action available to actors within power’s existing boundaries, and second, to shift the formation of the boundaries themselves to provide new conditions for future agency.
Keywords: Poor children; Bangladesh; Dhaka; Power (Social sciences)